The ratio of different orientation in the process of development of physical abilities of the students of the 1st course. - Volkov V.L (Kharkov National Pedagogical University, 2012)
The problem of management of the educational process of the development of physical abilities of the student youth is considered. Investigated the status of physical training of 168 students of pedagogical specialities aged 17 and 18 years, as well as studied age-related peculiarities of the development of physical abilities of the future specialists. The structure of physical training of 17 years' youth, which consists of five orthogonal factors, and the amount of their contributions is 86,4%. Developed planning of the amount of physical loads of different directions for the full and harmonious physical development of the students, who are studying at the first course in the conditions of the major medical groups for physical education. The presented methodological recommendations include introduction of means, which are directed on development of eight major physical abilities and some forms of their manifestation, which allows appropriate use of various physical exercises in accordance with the natural development of an organism of young men.